A high-toughness ultra-high-temperature ceramic-based composite material and its preparation method
By using the synergistic toughening method of BN nanotubes and carbon fibers, combined with a specific process to prepare a hafnium-zirconium-carbon solid solution ceramic matrix, the problem of insufficient toughness and ablation resistance of ultra-high temperature ceramic-based composite materials in extreme environments was solved, and the high toughness and temperature resistance of the material were improved.
Patent Information
- Application Number
- CN202411754210.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-09-23
- Estimated Expiration
- 2044-12-02
AI Technical Summary
Existing carbon fiber-reinforced ultra-high temperature ceramic-based composite materials lack toughness and ablation resistance in extreme environments, making it difficult to meet application requirements in high temperature and high pressure environments.
BN nanotubes and carbon fibers are used for synergistic toughening. BN nanotubes are evenly dispersed in the hafnium-zirconium composite ceramic precursor solution through chemical vapor deposition, sand milling and high-pressure homogenization dispersion technology. Combined with the precursor impregnation and cracking process and Joule heat ultrafast synthesis process, the hafnium-zirconium-carbon solid solution is prepared as the ceramic matrix.
It significantly improves the toughness and ablation resistance of ceramic-based composites, improves the temperature resistance and mechanical properties of the material, and makes it suitable for extreme environments.
Smart Images

Figure CN119569470B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ceramic-based composite material preparation, and in particular relates to a high-toughness ultra-high-temperature ceramic-based composite material and a preparation method thereof. Background Art
[0002] Carbon fiber-toughened ceramic-based composites have excellent properties such as light weight, high temperature resistance, and ablation resistance, and have received widespread attention. Carbon fiber-toughened ceramic-based composites mainly include components such as carbon fiber, interface layer, ceramic matrix, and coating. As a one-dimensional axially symmetrical micron-level material, carbon fiber can play a good role in toughening the ceramic matrix through fracture pullout and the like. At the mesoscopic scale, carbon fibers are evenly distributed inside the ceramic matrix, but at a more microscopic scale, the ceramic matrix is still brittle within the micron range. When there is a large stress, the ceramic matrix in this area still exhibits brittle fracture, which shows that the toughness of the carbon fiber-toughened ceramic-based composites is average. Therefore, how to further improve the mechanical properties of ceramic-based composites, improve the toughness of the ceramic matrix at the microscale, and ensure its comprehensive performance in extreme environments has become a key research issue in this technical field.
[0003] Furthermore, zirconium carbide and hafnium carbide are two common ultra-high temperature ceramics with extremely high melting points, making them suitable as the ceramic matrix for ultra-high temperature ceramic matrix composites. However, currently developed ultra-high temperature ceramic matrix composites based on zirconium carbide and / or hafnium carbide also have insufficient ablation resistance in extreme environments and also suffer from insufficient toughness.
[0004] In summary, it is very necessary to provide a high-toughness ultra-high temperature ceramic-based composite material and a preparation method thereof. Summary of the Invention
[0005] In order to solve one or more technical problems existing in the prior art, the present invention provides a high-toughness ultra-high temperature ceramic matrix composite material and a preparation method thereof. The method of the present invention uses BN nanotubes as a microscopic toughening phase, which synergistically exerts a toughening effect with carbon fibers, greatly improving the toughness of the ultra-high temperature ceramic matrix, thereby improving the toughness of the ceramic matrix composite material finally prepared. At the same time, the present invention uses a new hafnium-zirconium composite ceramic precursor solution as a reactant. After the precursor impregnation and cracking process, a high-performance hafnium-zirconium-carbon solid solution can be obtained as the ceramic matrix of the ceramic matrix composite material, which can also improve the mechanical properties of the ceramic matrix composite material, improve the toughness of the material, and also help to improve the temperature resistance and ablation resistance of the ceramic matrix composite material, solving the problem that the carbon fiber reinforced ultra-high temperature ceramic matrix composite material prepared by traditional technology has general toughness, and the temperature resistance and / or ablation resistance needs to be further improved.
[0006] In a first aspect, the present invention provides a method for preparing a high-toughness ultrahigh-temperature ceramic-based composite material, the method comprising the following steps:
[0007] (1) preparing a high thermal conductivity fiber preform;
[0008] (2) preparing an interface layer on the fiber surface of the high thermal conductivity fiber preform by chemical vapor deposition to obtain a porous carbon / carbon matrix;
[0009] (3) uniformly dispersing boron nitride nanotubes in a hafnium-zirconium composite ceramic precursor solution by sand milling and high-pressure homogenization dispersion technology to obtain a boron nitride nanotube-reinforced hafnium-zirconium composite ceramic precursor solution;
[0010] (4) The hafnium-zirconium composite ceramic precursor solution reinforced with boron nitride nanotubes was reacted with a porous carbon / carbon matrix through a precursor impregnation and cracking process to produce a high-toughness ultra-high-temperature ceramic-based composite material.
[0011] In a second aspect, the present invention provides a high-toughness ultra-high-temperature ceramic-based composite material produced by the preparation method described in the first aspect of the present invention.
[0012] Compared with the prior art, the present invention has at least the following beneficial effects:
[0013] (1) The present invention uses BN nanotubes (boron nitride nanotubes) as the microscopic toughening phase of the ceramic matrix, which works synergistically with carbon fibers to significantly improve the toughness of ceramic-based composite materials. Unlike carbon nanotubes, which are carbon materials and will participate in the carbothermal reduction reaction, resulting in damage to their microstructure and inability to effectively exert their toughening effect, the present invention uses BN nanotubes for toughening. When a new hafnium-zirconium composite ceramic precursor solution is subsequently used to prepare the hafnium-zirconium-carbon solid solution, the BN nanotubes will not participate in the carbothermal reduction reaction, resulting in no damage to their microstructure and can effectively exert their toughening effect.
[0014] (2) The present invention adopts a specific sand milling and high-pressure homogenization dispersion technology to prepare the BN nanotube-reinforced hafnium-zirconium composite ceramic precursor solution. The BN nanotubes can form intermolecular forces with the non-polar functional groups in the polymer molecules of the hafnium-zirconium composite ceramic precursor, thereby achieving effective dispersion of the BN nanotubes. After the precursor is impregnated and cracked, the BN nanotubes can also be ensured to be uniformly dispersed within the hafnium-zirconium-carbon solid solution matrix, thereby maximizing the toughening effect.
[0015] (3) The present invention obtains a novel hafnium-zirconium composite ceramic precursor solution in which hafnium and zirconium are mixed at the atomic level by mixing hafnium propyl ester and zirconium propyl ester and then undergoing coordination reaction and co-hydrolysis reaction. A hafnium-zirconium-carbon solid solution can be formed as a ceramic matrix in the ceramic-based composite material by impregnation and cracking of the precursor. The present invention finds that the hafnium-zirconium-carbon solid solution ceramic matrix obtained in the ceramic-based composite material by using the BN nanotube-reinforced hafnium-zirconium composite ceramic precursor solution has an ultra-high melting point and better ablation resistance than the mixed matrix of hafnium carbide and zirconium carbide obtained by using other hafnium-zirconium precursor solutions as reactants. It can greatly improve the temperature resistance and ablation resistance of the ceramic-based composite material, and is also more conducive to improving the mechanical properties and toughness of the ceramic-based composite material.
[0016] (4) In some preferred embodiments of the present invention, after the precursor impregnation and cracking process, the process further includes a step of performing multiple annealing treatments using a Joule heat ultrafast synthesis process. The present invention has found that performing multiple rapid annealing treatments using a Joule heat ultrafast synthesis process can promote matrix recrystallization and densification through uniform high-temperature rapid heat treatment, and can induce the redistribution of ceramic grain boundaries of the ceramic-based composite material to form a grain boundary structure that is more conducive to toughness. Joule heat rapid annealing is beneficial to retaining the fine grain structure of the material and is more conducive to promoting the formation of a high-temperature stable phase, thereby improving the mechanical properties, toughness, temperature resistance and ablation resistance of the finally prepared ceramic-based composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a preparation flow chart for preparing high-toughness ultra-high temperature ceramic-based composite materials according to some specific embodiments of the present invention.
[0018] Figure 2 Schematic diagram of a wedge-shaped high thermal conductivity fiber preform produced according to some specific embodiments of the present invention. DETAILED DESCRIPTION
[0019] To make the objectives, technical solutions, and advantages of the present invention more clear, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the embodiments described are part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0020] In the first aspect, the present invention provides a method for preparing a high-toughness ultra-high temperature ceramic-based composite material. The preparation flow chart is as follows: Figure 1 As shown, the method includes the following steps:
[0021] (1) Preparing a high thermal conductivity fiber preform; the present invention can use conventional weaving techniques such as suturing and puncturing (such as fine weaving puncturing) to prepare a high thermal conductivity fiber preform; preferably, the high thermal conductivity fiber preform is made of thin-diameter mesophase pitch-based carbon fiber. The fiber diameter of general mesophase pitch-based carbon fiber can generally reach 14 μm, showing poor flexibility. In the subsequent weaving process, the broken wire ratio is high, which leads to the mechanical properties of the final ceramic-based composite material being affected; the present invention preferably uses thin-diameter mesophase pitch-based carbon fiber with a diameter of 7-9 μm, a tensile strength of 2-3 GPa, and a thermal conductivity of 600-800 W / m·K to weave the high thermal conductivity fiber preform. The present invention does not make specific restrictions on the source of the thin-diameter mesophase pitch-based carbon fiber, which is an existing known material. In the present invention, the thin-diameter mesophase pitch-based carbon fiber can be, for example, from Shaanxi Tiance New Materials Technology Co., Ltd.;
[0022] (2) preparing an interface layer on the fiber surface of the high thermal conductivity fiber preform by chemical vapor deposition to obtain a porous carbon / carbon matrix; the present invention does not specifically limit the process conditions of the chemical vapor deposition method, and those skilled in the art can routinely select;
[0023] (3) Boron nitride nanotubes (BN nanotubes) are uniformly dispersed in a hafnium zirconium composite ceramic precursor solution by sand milling and high-pressure homogenous dispersion technology to obtain a hafnium zirconium composite ceramic precursor solution reinforced with boron nitride nanotubes; the present invention uses a specific sand milling and high-pressure homogenous dispersion technology to more uniformly disperse boron nitride nanotubes in a hafnium zirconium composite ceramic precursor solution, and its dispersion effect is significantly better than the existing stirring and / or ultrasonic dispersion technology; the present invention finds that the present invention can form intermolecular forces between BN nanotubes and non-polar functional groups in the polymer molecules of the hafnium zirconium composite ceramic precursor by adopting a specific sand milling and high-pressure homogenous dispersion technology, thereby achieving effective dispersion of BN nanotubes, and after the precursor is impregnated and cracked, it can also ensure that the BN nanotubes are uniformly dispersed inside the hafnium zirconium carbon solid solution matrix, thereby maximizing the toughening effect; however, if conventional stirring and ultrasonic treatment are used, the forces between the BN nanotubes cannot be effectively overcome, and large agglomerates still exist;
[0024] (4) reacting a boron nitride nanotube-reinforced hafnium-zirconium composite ceramic precursor solution with a porous carbon / carbon matrix through a precursor impregnation and cracking process to obtain a high-toughness ultrahigh-temperature ceramic-based composite material; that is, in step (4), the boron nitride nanotube-reinforced hafnium-zirconium composite ceramic precursor solution is used as a reactant to compound the porous carbon / carbon matrix, and the high-toughness ultrahigh-temperature ceramic-based composite material is prepared through a precursor impregnation and cracking method; in the present invention, the high toughness of the ultrahigh-temperature ceramic-based composite material, for example, refers to a fracture toughness greater than or equal to 25 MPa·m at room temperature. 1 / 2 .
[0025] The present invention uses BN nanotubes (boron nitride nanotubes) as the microscopic toughening phase of the ceramic matrix, and works in conjunction with carbon fibers to significantly improve the toughness of ceramic-based composites. Unlike carbon nanotubes, which are carbon materials and participate in carbon thermal reduction reactions, which damage their microstructure and prevent them from effectively exerting their toughening effect, the present invention uses BN nanotubes for toughening. When a novel hafnium-zirconium composite ceramic precursor solution is subsequently used to prepare a hafnium-zirconium carbon solid solution, the carbon thermal reduction reaction will not be involved, and the microstructure will not be damaged, which effectively enhances their toughening effect. The present invention obtains the BN nanotube-enhanced hafnium-zirconium composite ceramic precursor solution by adopting specific sand milling and high-pressure homogenization and dispersion technology. The BN nanotubes can form intermolecular forces with the non-polar functional groups in the polymer molecules of the hafnium-zirconium composite ceramic precursor, thereby achieving effective dispersion of the BN nanotubes. After the precursor is impregnated and cracked, it can also ensure that the BN nanotubes are uniformly dispersed inside the hafnium-zirconium carbon solid solution matrix, maximizing toughening effect.
[0026] According to some preferred embodiments, in step (1): the high thermal conductivity fiber preform is made of thin-diameter mesophase pitch-based carbon fibers, the diameter of the thin-diameter mesophase pitch-based carbon fibers is 7-9 μm, the tensile strength is 2-3 GPa, and the thermal conductivity is 600-800 W / m·K; generally speaking, the smaller the fiber diameter, the better its flexibility; but when the diameter of the mesophase pitch-based carbon fibers is lower than 7 μm, its tensile strength is difficult to meet the requirements of weaving, which easily leads to a high rate of broken fibers in the high thermal conductivity fiber preform; and when the diameter is higher than 9 μm, the fiber flexibility is poor, which also leads to a high rate of broken fibers in the high thermal conductivity fiber preform; the present invention adopts thin-diameter mesophase pitch-based carbon fibers with a diameter of 7-9 μm, a tensile strength of 2-3 GPa, and a thermal conductivity of 600-800 W / m·K, which has high weavability and helps to improve the mechanical properties and thermal conductivity of ceramic-based composite materials; and / or the density of the high thermal conductivity fiber preform is 0.7-1.0 g / cm 3 .
[0027] According to some preferred embodiments, in step (2): the density of the porous carbon / carbon matrix is 0.9 to 1.2 g / cm 3 ; and / or the interface layer is one or more of a pyrolytic carbon interface layer, a boron nitride interface layer, and a silicon carbide interface layer; the present invention does not specifically limit the process conditions for depositing the interface layer, which is a conventional technique in the art. The density of the porous carbon / carbon matrix after depositing the interface layer can be 0.9 to 1.2 g / cm by adjusting the volume percentage and / or thickness of the interface layer, which is preferably a pyrolytic carbon interface layer, by using chemical vapor deposition technology. 3 .
[0028] According to some preferred embodiments, step (3) is: adding boron nitride nanotubes (BN nanotubes) to a hafnium-zirconium composite ceramic precursor solution and sand-milling to obtain a coarse dispersion, and then high-pressure homogenizing and dispersing the coarse dispersion to obtain a fine dispersion, which is the boron nitride nanotube-enhanced hafnium-zirconium composite ceramic precursor solution; the sand-milling time is 30 to 60 minutes, the sand-milling speed is 1000-3000 r / min, the particle size of the zirconium beads used in the sand-milling is 1 to 3 mm, and the zirconium bead filling rate is 50-70%; the pressure of the high-pressure homogenizing dispersion is 35 to 100 MPa, the time of the high-pressure homogenizing dispersion is 15 to 60 minutes, and the temperature is 25 to 60°C; in the present invention, the high-pressure homogenizing dispersion is carried out, for example, in a high-pressure homogenizer.
[0029] Due to the strong van der Waals forces between BN nanotubes, they are easily entangled or agglomerated into bundles, which limits their uniform dispersion effect. The present invention first adopts the above-mentioned specific sand grinding conditions to achieve coarse dispersion of BN nanotubes in the hafnium-zirconium composite ceramic precursor solution, and then adopts the above-mentioned specific high-pressure homogeneous dispersion technology to achieve fine dispersion of BN nanotubes. The stable hydraulic boosting technology is used to increase the pressure of the dispersion liquid. In the microchannel, the dispersion liquid is subjected to ultra-high frequency physical shearing, collision and other physical forces. The BN nanotubes can form intermolecular forces with the non-polar functional groups in the polymer molecules of the hafnium-zirconium composite ceramic precursor, thereby achieving effective dispersion of the BN nanotubes, effectively avoiding BN nanotube agglomeration, and uniformly dispersing the BN nanotubes in the hafnium-zirconium composite ceramic precursor solution to form a BN nanotube-reinforced hafnium-zirconium composite ceramic precursor solution.
[0030] According to some preferred embodiments, in step (3): the length of the boron nitride nanotubes (boron nitride nanotube powder) is less than or equal to 300 nm, preferably 200-300 nm, and the aspect ratio is greater than or equal to 60, preferably 60-100; the present invention does not specifically limit the source of the boron nitride nanotubes, which are existing known materials, for example, can be provided by the Beijing Graphene Research Institute; in the present invention, preferably, the aspect ratio of the BN nanotubes is not less than 60, and the length is not greater than 300 nm. The present invention found that when the aspect ratio of the BN nanotubes is not less than 60, it can ensure that the BN nanotubes have a one-dimensional tubular structure, which can be compared with the mesoscopic carbon fiber. The two dimensions form a synergistic effect, which plays a toughening role at the mesoscopic and macroscopic scales respectively. When the aspect ratio of the BN nanotubes is less than 60, the one-dimensional structure is not obvious. When the crack propagation path extends to the boron nitride nanotubes, the energy consumed in pulling out the BN nanotubes is small, and the toughening effect cannot be effectively achieved. When the length of the BN nanotubes is not more than 300 nm, it can ensure that the BN nanotubes are smoothly impregnated into the pores of the porous carbon / carbon matrix, thereby achieving effective filling. However, when the length of the BN nanotubes is greater than 300 nm, the filling amount of the BN nanotubes is affected by the pore size in the porous carbon / carbon matrix, thereby affecting the mechanical properties of the finally prepared ceramic-based composite material.
[0031] According to some preferred embodiments, in step (3), the hafnium-zirconium composite ceramic precursor solution is prepared as follows: propyl hafnate (i.e., tetrapropyl hafnate) and propyl zirconate (i.e., n-propyl zirconate) are mixed uniformly with xylene, and then ninhydrin is added as a ligand and phenolic epoxy vinyl ester resin is added and mixed uniformly to obtain a mixed solution, and the mixed solution is reacted in an argon atmosphere of 5°C to 10°C for 100 to 150 minutes to obtain the hafnium-zirconium composite ceramic precursor solution; the present invention does not specifically limit the phenolic epoxy vinyl ester resin, and a product directly purchased or a product synthesized by an existing method can be used; in the present invention, the propyl hafnate and the zirconium The amount of propyl zirconate is such that the molar ratio of hafnium in the propyl zirconate to zirconium in the propyl zirconate is (0.1-99.9): (0.1-99.9); the molar amount of ninhydrin is 0.5-0.8 times the sum of the molar amounts of the propyl zirconate and the propyl zirconate; the molar amount of the phenolic epoxy vinyl ester resin is 1.5-3 times the sum of the molar amounts of the propyl zirconate and the propyl zirconate; the amount of xylene is such that the solid content of the hafnium-zirconium composite ceramic precursor solution is 45-65% and the viscosity is 50-90 mPa·s; in the present invention, the solid content is the amount of the remaining portion of the hafnium-zirconium composite ceramic precursor solution after solidification. The invention discloses a novel hafnium-zirconium composite ceramic precursor solution comprising a mixture of hafnium propyl ester and zirconate and a coordination reaction and a co-hydrolysis reaction to obtain a novel hafnium-zirconium composite ceramic precursor solution in which hafnium and zirconium are mixed at the atomic level. In the hafnium-zirconium composite ceramic precursor solution, hafnium and zirconium are on the same main chain, thereby achieving atomic-level mixing. In the invention, since hafnium and zirconium are associated elements, their properties are similar and their atomic diffusion coefficients are relatively large, thus achieving crystal atomic replacement. Furthermore, the invention adopts ninhydrin as a ligand, which has three binding sites. Compared with the use of ligands such as acetylacetone, the distribution of hafnium propyl ester and zirconate can be ensured to be more uniform, thereby achieving a better performance of the polyhafnium zirconium precursor solution. The ratio of hafnium to zirconium in the main chain of hafnium zirconium oxane is more precise, which effectively avoids excessive aggregation of a certain component, resulting in large differences in the atomic composition of the hafnium-zirconium-carbon solid solution in different regions. In addition, the present invention takes into account the difference in molar mass of hafnium and zirconium, and by extending the reaction time in the low-temperature argon environment, it can ensure that the reaction is sufficiently sufficient and uniform, and also ensure that the ratio of hafnium to zirconium in the main chain of polyhafnium zirconium oxane is more precise. The present invention has found that it is precisely the atomic-level mixed hafnium-zirconium composite ceramic precursor solution prepared by the above method that can ensure a more precise ratio of hafnium to zirconium in the main chain of polyhafnium zirconium oxane, and after solidification and high-temperature cracking treatment, a hafnium-zirconium-carbon solid solution can be obtained as a ceramic matrix in a ceramic-based composite material.The present invention finds that the hafnium-zirconium composite ceramic precursor solution reinforced with BN nanotubes is used to obtain a hafnium-zirconium-carbon solid solution ceramic matrix in a ceramic-based composite material. Compared with a mixed matrix of hafnium carbide and zirconium carbide obtained by using other hafnium-zirconium precursor solutions as reactants, the hafnium-zirconium-carbon solid solution ceramic matrix has an ultra-high melting point and better ablation resistance. This can significantly improve the temperature resistance and ablation resistance of the ceramic-based composite material, and is also more conducive to improving the mechanical properties and toughness of the ceramic-based composite material.
[0032] According to some preferred embodiments, in step (3): the solid content of the hafnium-zirconium composite ceramic precursor solution is 45-65%, and the viscosity is 50-90 mPa·s; the volume percentage (volume fraction) of boron nitride nanotubes in the boron nitride nanotube-enhanced hafnium-zirconium composite ceramic precursor solution is 0.1-5%; the molar ratio (atomic molar ratio) of hafnium to zirconium in the hafnium-zirconium composite ceramic precursor solution is (0.1-99.9): (0.1-99.9); and / or the hafnium-zirconium composite ceramic precursor solution forms a hafnium-zirconium-carbon solid solution as a ceramic matrix during the precursor impregnation and cracking process.
[0033] The present invention does not specifically limit the impregnation, curing and cracking conditions specifically used in the precursor impregnation, curing and cracking process, and those skilled in the art can make routine selections. The present invention uses a boron nitride nanotube-reinforced hafnium-zirconium composite ceramic precursor solution as a reactant, and fills the boron nitride nanotube-reinforced hafnium-zirconium composite ceramic precursor solution into the pores through vacuum and pressure impregnation. After heating at 150-350°C, the ceramic precursor can be completely cured, and then undergoes a high-temperature cracking process. The above impregnation-curing-cracking process is repeated to finally obtain a high-toughness ultra-high-temperature ceramic-based composite material.
[0034] According to some preferred embodiments, step (4) includes the following sub-steps:
[0035] (a) placing a porous carbon / carbon substrate in a boron nitride nanotube-reinforced hafnium-zirconium composite ceramic precursor solution and impregnating it for 10 to 360 minutes, filling the boron nitride nanotube-reinforced hafnium-zirconium composite ceramic precursor solution into the internal pores to obtain a material impregnated with the boron nitride nanotube-reinforced hafnium-zirconium composite ceramic precursor solution; preferably, the impregnation is vacuum impregnation and pressure impregnation; the present invention does not specifically limit the process parameters of vacuum impregnation and pressure impregnation, which are well known to those skilled in the art and can be carried out using conventional parameters;
[0036] (b) curing the material impregnated with the boron nitride nanotube-enhanced hafnium-zirconium composite ceramic precursor solution, for example, curing it under an inert atmosphere such as nitrogen and heating at 150-350° C., so that the boron nitride nanotube-enhanced hafnium-zirconium composite ceramic precursor solution inside the pores can be cross-linked and cured, and then placing the cured material in a reaction device, sealing it, evacuating it, and introducing an inert gas such as nitrogen or other inert gas, the flow rate of which can be, for example, 500-5000 sccm, and heating it by program control, and cracking it at 1500-1800° C., preferably 1600-1800° C., for 10-600 min; preferably, the curing is curing at 150-350° C. for 10-360 min; in the present invention, the heating rate to 150-350° C. and / or 1500-1800° C. can be, for example, 1-10° C. / min;
[0037] (c) After the cracking reaction in step (b) is completed, the temperature is controlled to be lowered, and after cooling to room temperature, the introduction of the inert gas is stopped, and the pressure is restored to atmospheric pressure; in the present invention, the cooling rate can be, for example, 1 to 5°C / minute;
[0038] (d) Repeating steps (a) to (c) at least once, for example, multiple times (twice or more), preferably 1 to 10 times.
[0039] According to some preferred embodiments, in step (4), after the precursor impregnation and cracking process is performed, the process further includes the step of performing multiple annealing treatments using a Joule heat ultrafast synthesis process; the Joule heat ultrafast synthesis process is performed in a Joule ultrafast heating device (Joule ultrafast heating device), and the heating rate of each annealing treatment is 180 to 260°C / s (for example, 180°C / s, 190°C / s, 200°C / s, 210°C / s, 220°C / s, 2 30℃ / s, 240℃ / s, 250℃ / s or 260℃ / s), the annealing temperature is 1600-2000℃ (for example, 1600℃, 1700℃, 1800℃, 1900℃ or 2000℃), the holding time of each annealing is 2-5min (for example, 2, 3, 4 or 5min), and after the holding is completed, it is naturally cooled to room temperature and then the next annealing treatment is performed; the number of annealing treatments is 3-5 times (for example, 3, 4 or 5 times).
[0040] The present invention preferably includes the step of performing multiple annealing treatments using a Joule heat ultrafast synthesis process after the precursor impregnation and cracking process. The present invention finds that performing multiple rapid annealing treatments using a Joule heat ultrafast synthesis process can promote matrix recrystallization and densification through uniform high-temperature rapid heat treatment, and can induce the ceramic grain boundaries of the ceramic-based composite material to be redistributed to form a grain boundary structure that is more conducive to toughness. Joule heat rapid annealing is beneficial to retaining the fine grain structure of the material and is more conducive to promoting the formation of a high-temperature stable phase, thereby helping to improve the mechanical properties, toughness, temperature resistance and ablation resistance of the finally prepared ceramic-based composite material.
[0041] According to some preferred embodiments, in step (1): the high thermal conductivity fiber preform is a pointed wedge-shaped high thermal conductivity fiber preform. In the present invention, the structure of the pointed wedge-shaped high thermal conductivity fiber preform is as follows. Figure 2 As shown; the preparation of the pointed wedge-shaped high thermal conductivity fiber preform is: mixing the thin-diameter mesophase pitch-based carbon fiber and the PAN-based carbon fiber to obtain the thin-diameter mesophase pitch-based carbon fiber / carbon fiber bidirectional cloth, and then using a lamination and stitching process to make the thin-diameter mesophase pitch-based carbon fiber / carbon fiber bidirectional cloth into a pointed wedge-shaped high thermal conductivity fiber preform; in the present invention, when the pointed wedge-shaped high thermal conductivity fiber preform is used, the high-toughness ultra-high temperature ceramic-based composite material obtained is in a pointed wedge shape.
[0042] Since the fiber diameter of general mesophase pitch-based carbon fibers can generally reach 14μm, they show poor flexibility and are difficult to meet large bending requirements. As a result, the existing preforms woven with general mesophase pitch-based carbon fibers and / or PAN-based carbon fibers are usually flat preforms. However, the ceramic-based composite materials currently made using this conventional structural preform are in the shape of a flat plate. This conventional shape cannot meet the application requirements in certain specific scenarios. In order to obtain a ceramic-based composite material of a specific shape, the traditional preparation technology usually first prepares a flat-plate ceramic-based composite material and then processes it into a specific shape. This method that requires reprocessing leads to a large waste of ceramic-based composite materials and problems of fiber breakage and discontinuity of fibers. Ultimately, the ceramic-based composite materials of a specific shape prepared by traditional technology have deficiencies in terms of thermal conductivity, ablation resistance and / or mechanical properties.
[0043] The present invention preferably designs a fiber preform of a novel structure, that is, a pointed wedge-shaped high thermal conductivity fiber preform is used as a preform for a ceramic-based composite material. The main structural feature of the pointed wedge-shaped high thermal conductivity fiber preform in the present invention is that along a certain fiber direction, the surface of the preform gradually becomes pointed, and the geometric shape is a pointed wedge (a shape in which one end of the preform is pointed and the other end is thick). One end of the pointed wedge-shaped high thermal conductivity fiber preform of the present invention is a pointed end area, and the other end is a thick end area. The present invention finds that the use of such a pointed wedge-shaped preform can obtain a directly integrated pointed wedge-shaped ceramic-based composite material. The pointed wedge-shaped ceramic-based composite material has better structural adaptability and functionality in specific application scenarios, and such a pointed wedge-shaped structure can improve the stress distribution and local strengthening effect of the material. In certain applications, the pointed wedge shape contributes to the optimal fluid flow. ization, reducing frictional resistance, especially in the fields of aerospace, power machinery, etc., the pointed wedge-shaped structure can effectively improve the flow state of airflow and liquid flow, improve energy efficiency, and can better disperse the concentrated area of external force, reduce crack propagation, and improve fatigue resistance under high temperature and high pressure environment; the present invention can realize the weaving of the pointed wedge-shaped high thermal conductivity fiber preform by mixing the fine-diameter mesophase pitch-based carbon fiber and carbon fiber, which gives full play to the high flexibility and high thermal conductivity of the fine-diameter mesophase pitch-based carbon fiber, while the simple PAN-based and general asphalt-based carbon fiber cannot meet the design requirements due to their poor flexibility; and the present invention can realize the controllable adjustment of the thermal conductivity and mechanical properties of the finally prepared ceramic-based composite material by regulating the volume ratio of the fine-diameter mesophase pitch-based carbon fiber to the carbon fiber in the pointed wedge-shaped high thermal conductivity fiber preform.
[0044] The present invention preferably uses a pointed wedge-shaped high-thermal conductivity fiber preform to directly integrate and form a pointed wedge-shaped ceramic-based composite material, which can take into account both fiber continuity and cost economy, and better ensure the thermal conductivity and mechanical properties of the ceramic-based composite material. This is also something that cannot be achieved by using a ceramic-based composite material made of a conventional structural preform and then processing it into a pointed wedge-shaped product after molding. This is because this method of first molding the ceramic-based composite material and then processing it into a product of a specific shape will cause the fibers in the tip area of the product to no longer be continuous. At the same time, there is a large waste in the preparation process, and there are problems with the thermal conductivity, ablation resistance and mechanical properties of the obtained ceramic-based composite material.
[0045] According to some preferred embodiments, the diameter of the thinned mesophase asphalt-based carbon fiber used in the pointed wedge-shaped high thermal conductivity fiber preform is 7-9 μm, the tensile strength is 2-3 GPa, and the thermal conductivity is 600-800 W / m·K, indicating that it has excellent flexibility and can meet the nearly 180° bending of the tip area of the pointed wedge-shaped high thermal conductivity fiber preform without breaking, thereby realizing the weaving of the pointed wedge-shaped high thermal conductivity fiber preform.
[0046] According to some preferred embodiments, in the thin-diameter mesophase pitch-based carbon fiber / carbon fiber bidirectional cloth, the thin-diameter mesophase pitch-based carbon fiber and the PAN-based carbon fiber are vertically distributed, that is, when the thin-diameter mesophase pitch-based carbon fiber / carbon fiber bidirectional cloth is mixed, the thin-diameter mesophase pitch-based carbon fiber and the PAN-based carbon fiber are perpendicular to each other; and / or the surface density of the thin-diameter mesophase pitch-based carbon fiber / carbon fiber bidirectional cloth is 300-400 g / m 2 When the thin-diameter mesophase asphalt-based carbon fiber / carbon fiber bidirectional cloth is mixed in the present invention, the ratio of the thin-diameter mesophase asphalt-based carbon fiber to the PAN-based carbon fiber can be adjusted to meet the subsequent weaving of a pointed wedge-shaped high thermal conductivity fiber preform with a specific volume ratio of thin-diameter mesophase asphalt-based carbon fiber to PAN-based carbon fiber.
[0047] According to some preferred embodiments, the lamination and stitching process is: first, the thin-diameter mesophase pitch-based carbon fiber / carbon fiber bidirectional cloth is folded in half along a direction perpendicular to the thin-diameter mesophase pitch-based carbon fiber, and then multiple pieces (two or more pieces) of the folded thin-diameter mesophase pitch-based carbon fiber / carbon fiber bidirectional cloth are stacked and stitched to obtain a wedge-shaped high thermal conductivity fiber preform; in the present invention, when laminating, the tips of the folded thin-diameter mesophase pitch-based carbon fiber / carbon fiber bidirectional cloth are made to correspond to the tips, and the thick ends are made to correspond to the thick ends, and then PAN-based carbon fiber is used to stitch the multiple folded thin-diameter mesophase pitch-based carbon fiber / carbon fiber bidirectional cloths into one piece; the present invention does not make specific restrictions on the stitching method used, and those skilled in the art can make conventional choices, for example, an orthogonal stitching method can be selected; the present invention does not make specific restrictions on the number of pieces of thin-diameter mesophase pitch-based carbon fiber / carbon fiber bidirectional cloth used for stacking, and those skilled in the art can make conventional choices based on the thickness requirements of the wedge-shaped high thermal conductivity fiber preform.
[0048] According to some preferred embodiments, the volume ratio of the tapered mesophase pitch-based carbon fibers to the PAN-based carbon fibers in the pointed wedge-shaped high thermal conductivity fiber preform is (1-3):(1-3).
[0049] In the second aspect, the present invention provides a high-toughness ultra-high temperature ceramic-based composite material prepared by the preparation method described in the first aspect of the present invention; the high-toughness ultra-high temperature ceramic-based composite material prepared by the present invention comprises a hafnium-zirconium-carbon solid solution ceramic matrix, and has advantages such as excellent mechanical properties and ablation resistance, which are manifested in a significant improvement in room temperature mechanical properties (room temperature toughness) and a significant reduction in the online ablation rate under an oxyacetylene ablation environment.
[0050] According to some preferred embodiments, the density of the high-toughness ultra-high temperature ceramic-based composite material is 3.0 to 5.0 g / cm 3and / or the high toughness ultra-high temperature ceramic-based composite material has a fracture toughness greater than or equal to 25 MPa·m at room temperature 1 / 2 .
[0051] The present invention will be further described below by way of examples, but the scope of protection of the present invention is not limited to these embodiments. The present invention may also have various other embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art may make various corresponding changes and modifications based on the present invention, but these corresponding changes and modifications should all fall within the scope of protection of the claims attached to the present invention. Unless otherwise specified, the experimental methods used in the following examples and comparative examples are conventional methods. The materials, reagents, etc. used in the following examples and comparative examples, unless otherwise specified, can all be obtained from commercial channels.
[0052] Example 1
[0053] ① Preparation of high thermal conductivity fiber preform: Using fine weaving puncture process, we use thin-diameter mesophase pitch-based carbon fiber with a diameter of 7μm, tensile strength of 2.4GPa, and thermal conductivity of 800W / m·K as raw material to weave a high thermal conductivity fiber preform with a density of 0.8g / cm 3 A flat-plate-shaped high thermal conductivity fiber preform.
[0054] ② Preparation of porous carbon / carbon matrix: Chemical vapor deposition method was used to prepare pyrolytic carbon interface layer on the fiber surface of high thermal conductivity fiber preform, and the density of the prepared porous carbon / carbon matrix was 1.0 g / cm 3 porous carbon / carbon matrix.
[0055] ③ Preparation of boron nitride nanotube-enhanced hafnium-zirconium composite ceramic precursor solution: The average length of the BN nanotubes (boron nitride nanotubes) used is 280 nm, and the average aspect ratio is 70; in the hafnium-zirconium composite ceramic precursor solution used, the atomic molar ratio of hafnium to zirconium is 3:1, the solid content of the hafnium-zirconium composite ceramic precursor solution is 50%, and the viscosity is 55 mPa·s. The hafnium-zirconium composite ceramic precursor solution used is prepared by: mixing propyl hafnate and propyl zirconate (in an amount such that the content of propyl hafnate is 100%) with propyl zirconate (in an amount such that the content of propyl hafnium ... zirconate is 100%) with propyl zirconate (in an amount The hafnium and zirconium propyl zirconate molar ratio is 3:1) are uniformly mixed in xylene, and then ninhydrin as a ligand (the molar ratio of hafnium propyl ester, zirconate propyl ester and ninhydrin is 3:1:3) and phenolic epoxy vinyl ester resin (the molar ratio of hafnium propyl ester, zirconate propyl ester and phenolic epoxy vinyl ester resin is 3:1:10) are added and mixed uniformly to obtain a mixed solution, and the mixed solution is reacted in an argon atmosphere at 5°C for 120 minutes to obtain the hafnium-zirconium composite ceramic precursor solution uniformly mixed at the atomic level. The hafnium zirconium composite ceramic precursor solution is prepared by uniformly dispersing BN nanotubes in the hafnium zirconium composite ceramic precursor solution by sand milling and high-pressure homogenization dispersion technology to obtain a hafnium zirconium composite ceramic precursor solution reinforced with boron nitride nanotubes. Specifically, the boron nitride nanotubes are added to the hafnium zirconium composite ceramic precursor solution and sand milled to obtain a coarse dispersion solution, and then the coarse dispersion solution is subjected to high-pressure homogenization dispersion to obtain the boron nitride nanotubes. Enhanced hafnium-zirconium composite ceramic precursor solution, the boron nitride nanotube-enhanced hafnium-zirconium composite ceramic precursor solution contains 1% by volume of boron nitride nanotubes; the sand milling time is 40 minutes, the sand milling speed is 2000 r / min, the particle size of the zirconium beads used in the sand milling is 1.8 mm, and the zirconium bead filling rate is 60%; the pressure (homogeneous pressure) of the high-pressure homogenization dispersion is 68 MPa, the high-pressure homogenization dispersion time is 30 minutes, and the temperature is 50°C.
[0056] ④ Preparation of high-toughness ultra-high-temperature ceramic matrix composite material: Boron nitride nanotube reinforced hafnium zirconium composite ceramic precursor solution is used as a reactant to composite a porous carbon / carbon matrix, and a precursor impregnation and pyrolysis process is used to prepare a flat plate-shaped high-toughness ultra-high-temperature ceramic matrix composite material containing a hafnium zirconium carbon solid solution ceramic matrix. The precursor impregnation and pyrolysis process includes a specific impregnation-curing-pyrolysis process: the porous carbon / carbon matrix is placed in the boron nitride nanotube reinforced hafnium zirconium composite ceramic precursor solution and vacuum impregnated for 60 minutes and pressurized for 60 minutes in sequence to obtain a material impregnated with the boron nitride nanotube reinforced hafnium zirconium composite ceramic precursor solution. The vacuum impregnation pressure is 200 Pa, and the pressurized impregnation pressure is 1. 5MPa; then the obtained boron nitride nanotube reinforced hafnium zirconium composite ceramic precursor solution impregnated material is cured in a nitrogen atmosphere, the curing temperature is 260 ° C, the curing time at 260 ° C is 120min, the heating rate to 260 ° C is 5 ° C / min, then the cured material is placed in a reaction device, sealed, evacuated, and nitrogen inert gas is introduced with a flow rate of 1000sccm. The program is set to control the temperature, the heating rate is 5 ° C / min, and the material is cracked at 1600 ° C for 240min. After the cracking reaction is completed, the temperature is lowered at a rate of 5 ° C / min, cooled to room temperature, the nitrogen inert gas is turned off, and the material is restored to atmospheric pressure; the impregnation-curing-cracking process is repeated many times until a density of 3.9g / cm is obtained. 3 Flat-plate-shaped high-toughness ultra-high temperature ceramic matrix composite material.
[0057] The fracture toughness of the high-toughness ultra-high temperature ceramic matrix composite material obtained in this embodiment was measured to be 27.3 MPa·m at room temperature. 1 / 2 After the oxyacetylene ablation test at 2000℃ (ablation time is 500s), the linear ablation rate is 1.0×10 -4 mm / s.
[0058] Example 2
[0059] ① Preparation of high thermal conductivity fiber preform: Using fine weaving puncture process, we use thin-diameter mesophase pitch-based carbon fiber with a diameter of 7μm, tensile strength of 2.4GPa, and thermal conductivity of 800W / m·K as raw material to weave a high thermal conductivity fiber preform with a density of 0.8g / cm 3 A flat-plate-shaped high thermal conductivity fiber preform.
[0060] ② Preparation of porous carbon / carbon matrix: Chemical vapor deposition method was used to prepare pyrolytic carbon interface layer on the fiber surface of high thermal conductivity fiber preform, and the density of the prepared porous carbon / carbon matrix was 1.0 g / cm 3 porous carbon / carbon matrix.
[0061] ③ Preparation of boron nitride nanotube-enhanced hafnium-zirconium composite ceramic precursor solution: The average length of the BN nanotubes (boron nitride nanotubes) used is 280 nm, and the average aspect ratio is 70; in the hafnium-zirconium composite ceramic precursor solution used, the atomic molar ratio of hafnium to zirconium is 3:1, the solid content of the hafnium-zirconium composite ceramic precursor solution is 50%, and the viscosity is 55 mPa·s. The hafnium-zirconium composite ceramic precursor solution used is prepared by: mixing propyl hafnate and propyl zirconate (in an amount such that the content of propyl hafnate is 100%) with propyl zirconate (in an amount such that the content of propyl hafnium ... zirconate is 100%) with propyl zirconate (in an amount The hafnium and zirconium propyl zirconate molar ratio is 3:1) are uniformly mixed in xylene, and then ninhydrin as a ligand (the molar ratio of hafnium propyl ester, zirconate propyl ester and ninhydrin is 3:1:3) and phenolic epoxy vinyl ester resin (the molar ratio of hafnium propyl ester, zirconate propyl ester and phenolic epoxy vinyl ester resin is 3:1:10) are added and mixed uniformly to obtain a mixed solution, and the mixed solution is reacted in an argon atmosphere at 5°C for 120 minutes to obtain the hafnium-zirconium composite ceramic precursor solution uniformly mixed at the atomic level. The hafnium zirconium composite ceramic precursor solution is prepared by uniformly dispersing BN nanotubes in the hafnium zirconium composite ceramic precursor solution by sand milling and high-pressure homogenization dispersion technology to obtain a hafnium zirconium composite ceramic precursor solution reinforced with boron nitride nanotubes. Specifically, the boron nitride nanotubes are added to the hafnium zirconium composite ceramic precursor solution and sand milled to obtain a coarse dispersion solution, and then the coarse dispersion solution is subjected to high-pressure homogenization dispersion to obtain the boron nitride nanotubes. Enhanced hafnium-zirconium composite ceramic precursor solution, the boron nitride nanotube-enhanced hafnium-zirconium composite ceramic precursor solution contains 3% by volume of boron nitride nanotubes; the sand milling time is 40 minutes, the sand milling speed is 2000 r / min, the particle size of the zirconium beads used in the sand milling is 1.8 mm, and the zirconium bead filling rate is 60%; the pressure (homogeneous pressure) of the high-pressure homogenization dispersion is 68 MPa, the high-pressure homogenization dispersion time is 30 minutes, and the temperature is 50°C.
[0062] ④ Preparation of high-toughness ultra-high temperature ceramic-based composite materials: Boron nitride nanotube-reinforced hafnium zirconium composite ceramic precursor solution is used as a reactant to compound the porous carbon / carbon matrix, and a high-toughness ultra-high temperature ceramic-based composite material is prepared by a precursor impregnation and cracking process. The precursor impregnation and cracking process includes a specific impregnation-curing-cracking process: placing the porous carbon / carbon matrix in a boron nitride nanotube-reinforced hafnium zirconium composite ceramic precursor solution and sequentially performing vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes to obtain a material impregnated with a boron nitride nanotube-reinforced hafnium zirconium composite ceramic precursor solution, the vacuum impregnation pressure is 200Pa, and the pressurized impregnation pressure is 1.5MPa; then The obtained boron nitride nanotube reinforced hafnium zirconium composite ceramic precursor solution impregnated material was cured in a nitrogen atmosphere at a curing temperature of 260°C, a curing time of 120 minutes at 260°C, and a heating rate of 5°C / min to 260°C. The cured material was then placed in a reaction device, sealed, evacuated, and introduced with nitrogen inert gas at a flow rate of 1000 sccm. The temperature was set to be program-controlled at a heating rate of 5°C / min, and pyrolysis was performed at 1600°C for 240 minutes. After the pyrolysis reaction was completed, the temperature was lowered at a rate of 5°C / min, cooled to room temperature, the nitrogen inert gas was turned off, and the temperature was restored to atmospheric pressure. The impregnation-curing-pyrolysis process was repeated multiple times until a density of 3.9 g / cm was obtained. 3 Flat-plate-shaped high-toughness ultra-high temperature ceramic matrix composite material.
[0063] The fracture toughness of the high-toughness ultra-high temperature ceramic matrix composite material obtained in this embodiment was measured to be 31.2 MPa·m at room temperature. 1 / 2 After the oxyacetylene ablation test at 2000℃ (ablation time is 500s), the linear ablation rate is 1.2×10 -4 mm / s.
[0064] Example 3
[0065] ① Preparation of high thermal conductivity fiber preform: Using fine weaving puncture process, we use thin-diameter mesophase pitch-based carbon fiber with a diameter of 7μm, tensile strength of 2.4GPa, and thermal conductivity of 800W / m·K as raw material to weave a high thermal conductivity fiber preform with a density of 0.8g / cm 3 A flat-plate-shaped high thermal conductivity fiber preform.
[0066] ② Preparation of porous carbon / carbon matrix: Chemical vapor deposition method was used to prepare pyrolytic carbon interface layer on the fiber surface of high thermal conductivity fiber preform, and the density of the prepared porous carbon / carbon matrix was 1.0 g / cm 3 porous carbon / carbon matrix.
[0067] ③ Preparation of boron nitride nanotube-enhanced hafnium-zirconium composite ceramic precursor solution: The average length of the BN nanotubes (boron nitride nanotubes) used is 280 nm, and the average aspect ratio is 70; in the hafnium-zirconium composite ceramic precursor solution used, the atomic molar ratio of hafnium to zirconium is 3:1, the solid content of the hafnium-zirconium composite ceramic precursor solution is 50%, and the viscosity is 55 mPa·s. The hafnium-zirconium composite ceramic precursor solution used is prepared by: mixing propyl hafnate and propyl zirconate (in an amount such that the content of propyl hafnate is 100%) with propyl zirconate (in an amount such that the content of propyl hafnium ... zirconate is 100%) with propyl zirconate (in an amount The hafnium and zirconium propyl zirconate (the molar ratio of hafnium and zirconium propyl zirconate is 3:1) are uniformly mixed in xylene, and then ninhydrin as a ligand (the molar ratio of hafnium propyl ester, zirconate propyl and ninhydrin is 3:1:3) and a phenolic epoxy vinyl ester resin (the molar ratio of hafnium propyl ester, zirconate propyl and phenolic epoxy vinyl ester resin is 3:1:10) are added and mixed uniformly to obtain a mixed solution, and the mixed solution is reacted in an argon atmosphere at 5°C for 120 minutes to obtain the hafnium-zirconium composite ceramic precursor solution uniformly mixed at the atomic level. The amount of xylene is such that the solid content of the hafnium-zirconium composite ceramic precursor solution is 50% and the viscosity is 55 mPa·s; the BN nanotubes are uniformly dispersed in the hafnium-zirconium composite ceramic precursor solution by sand milling and high-pressure homogenization dispersion technology to obtain a boron nitride nanotube-reinforced hafnium-zirconium composite ceramic precursor solution, specifically, the boron nitride nanotubes are added to the hafnium-zirconium composite ceramic precursor solution and sand milled to obtain a coarse dispersion, and then the coarse dispersion is subjected to high-pressure homogenization dispersion to obtain the boron nitride nanotube-reinforced hafnium-zirconium composite ceramic precursor solution. The invention relates to a hafnium-zirconium composite ceramic precursor solution reinforced with boron nitride nanotubes, wherein the volume percentage of boron nitride nanotubes in the hafnium-zirconium composite ceramic precursor solution is 0.8%; the sand milling time is 40 minutes, the sand milling speed is 2000 r / min, the particle size of the zirconium beads used in the sand milling is 1.8 mm, and the zirconium bead filling rate is 60%; the pressure (homogeneous pressure) of the high-pressure homogenization dispersion is 68 MPa, the high-pressure homogenization dispersion time is 30 minutes, and the temperature is 50°C.
[0068] ④ Preparation of high-toughness ultra-high temperature ceramic-based composite materials: Boron nitride nanotube-reinforced hafnium zirconium composite ceramic precursor solution is used as a reactant to compound the porous carbon / carbon matrix, and a high-toughness ultra-high temperature ceramic-based composite material is prepared by a precursor impregnation and cracking process. The precursor impregnation and cracking process includes a specific impregnation-curing-cracking process: placing the porous carbon / carbon matrix in a boron nitride nanotube-reinforced hafnium zirconium composite ceramic precursor solution and sequentially performing vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes to obtain a material impregnated with a boron nitride nanotube-reinforced hafnium zirconium composite ceramic precursor solution, the vacuum impregnation pressure is 200Pa, and the pressurized impregnation pressure is 1.5MPa; then The obtained boron nitride nanotube reinforced hafnium zirconium composite ceramic precursor solution impregnated material was cured in a nitrogen atmosphere at a curing temperature of 260°C, a curing time of 120 minutes at 260°C, and a heating rate of 5°C / min to 260°C. The cured material was then placed in a reaction device, sealed, evacuated, and introduced with nitrogen inert gas at a flow rate of 1000 sccm. The temperature was set to be program-controlled at a heating rate of 5°C / min, and pyrolysis was performed at 1600°C for 240 minutes. After the pyrolysis reaction was completed, the temperature was lowered at a rate of 5°C / min, cooled to room temperature, the nitrogen inert gas was turned off, and the temperature was restored to atmospheric pressure. The impregnation-curing-pyrolysis process was repeated multiple times until a density of 3.9 g / cm was obtained. 3 Flat-plate-shaped high-toughness ultra-high temperature ceramic matrix composite material.
[0069] The fracture toughness of the high-toughness ultra-high temperature ceramic matrix composite material obtained in this embodiment was measured to be 25.4 MPa·m at room temperature. 1 / 2 After the oxyacetylene ablation test at 2000℃ (ablation time is 500s), the linear ablation rate is 0.9×10 -4 mm / s.
[0070] Example 4
[0071] ① Preparation of high thermal conductivity fiber preform: Using fine weaving puncture process, we use thin-diameter mesophase pitch-based carbon fiber with a diameter of 7μm, tensile strength of 2.4GPa, and thermal conductivity of 800W / m·K as raw material to weave a high thermal conductivity fiber preform with a density of 0.8g / cm 3 A flat-plate-shaped high thermal conductivity fiber preform.
[0072] ② Preparation of porous carbon / carbon matrix: Chemical vapor deposition method was used to prepare pyrolytic carbon interface layer on the fiber surface of high thermal conductivity fiber preform, and the density of the prepared porous carbon / carbon matrix was 1.0 g / cm 3 porous carbon / carbon matrix.
[0073] ③ Preparation of carbon nanotube-enhanced hafnium-zirconium composite ceramic precursor solution: the average length of the carbon nanotubes used is 280 nm, and the average aspect ratio is 70; the atomic molar ratio of hafnium to zirconium in the hafnium-zirconium composite ceramic precursor solution used is 3:1, the solid content of the hafnium-zirconium composite ceramic precursor solution is 50%, and the viscosity is 55 mPa·s. The hafnium-zirconium composite ceramic precursor solution used is prepared by: mixing propyl hafnate and propyl zirconate (in an amount such that the hafnium in the propyl hafnate and the propyl zirconate are 1:1) with each other. The hafnium zirconium composite ceramic precursor solution was obtained by uniformly mixing hafnium propyl ester, propyl zirconate and ninhydrin as a ligand (the molar ratio of hafnium propyl ester, propyl zirconate and ninhydrin was 3:1:3) and phenolic epoxy vinyl ester resin (the molar ratio of hafnium propyl ester, propyl zirconate and phenolic epoxy vinyl ester resin was 3:1:10) in xylene, and then adding ninhydrin as a ligand (the molar ratio of hafnium propyl ester, propyl zirconate and ninhydrin was 3:1:3) and mixing them uniformly to obtain a mixed solution, which was reacted in an argon atmosphere at 5°C for 120 minutes to obtain the hafnium zirconium composite ceramic precursor solution uniformly mixed at the atomic level. The hafnium zirconium composite ceramic precursor solution is prepared by mixing the carbon nanotubes with the hafnium zirconium composite ceramic precursor solution, and the amount of xylene is such that the solid content of the hafnium zirconium composite ceramic precursor solution is 50% and the viscosity is 55 mPa·s; the carbon nanotubes are uniformly dispersed in the hafnium zirconium composite ceramic precursor solution by sand milling and high-pressure homogenization dispersion technology to obtain a carbon nanotube-reinforced hafnium zirconium composite ceramic precursor solution, specifically, the carbon nanotubes are added to the hafnium zirconium composite ceramic precursor solution and sand milled to obtain a coarse dispersion liquid, and then the coarse dispersion liquid is subjected to high-pressure homogenization dispersion to obtain the carbon nanotube-reinforced hafnium zirconium composite ceramic precursor solution. A strong hafnium-zirconium composite ceramic precursor solution is prepared, wherein the volume percentage of carbon nanotubes in the carbon nanotube-reinforced hafnium-zirconium composite ceramic precursor solution is 1%; the sand milling time is 40 minutes, the sand milling speed is 2000 r / min, the particle size of the zirconium beads used in the sand milling is 1.8 mm, and the zirconium bead filling rate is 60%; the pressure (homogeneous pressure) of the high-pressure homogenization dispersion is 68 MPa, the high-pressure homogenization dispersion time is 30 minutes, and the temperature is 50°C.
[0074] ④ Preparation of ultra-high temperature ceramic-based composite materials: Using carbon nanotube-reinforced hafnium-zirconium composite ceramic precursor solution as a reactant, composite the porous carbon / carbon matrix, and prepare the ultra-high temperature ceramic-based composite material by precursor impregnation and cracking process. The precursor impregnation and cracking process includes a specific impregnation-curing-cracking process: placing the porous carbon / carbon matrix in the carbon nanotube-reinforced hafnium-zirconium composite ceramic precursor solution and sequentially performing vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes to obtain a material impregnated with the carbon nanotube-reinforced hafnium-zirconium composite ceramic precursor solution, the vacuum impregnation pressure is 200Pa, and the pressurized impregnation pressure is 1.5MPa; then the obtained carbon nanotubes are placed in the pre-curing process. The material impregnated with the tube-reinforced hafnium-zirconium composite ceramic precursor solution was cured in a nitrogen atmosphere at a curing temperature of 260°C, a curing time of 120 minutes at 260°C, and a heating rate of 5°C / min to 260°C. The cured material was then placed in a reaction device, sealed, evacuated, and introduced with nitrogen inert gas at a flow rate of 1000 sccm. The temperature was controlled by a program at a heating rate of 5°C / min and cracked at 1600°C for 240 minutes. After the cracking reaction was completed, the temperature was lowered at a rate of 5°C / min, cooled to room temperature, the nitrogen inert gas was turned off, and the temperature was restored to atmospheric pressure. The impregnation-curing-cracking process was repeated multiple times until a density of 3.9 g / cm was obtained. 3 Flat-plate ultra-high temperature ceramic matrix composite materials.
[0075] The fracture toughness of the ultra-high temperature ceramic matrix composite material prepared in this embodiment was measured to be 16.5 MPa·m at room temperature. 1 / 2 After the oxyacetylene ablation test at 2000℃ (ablation time is 500s), the linear ablation rate is 1.1×10 -4 mm / s.
[0076] Example 5
[0077] ① Preparation of high thermal conductivity fiber preform: Using fine weaving puncture process, we use thin-diameter mesophase pitch-based carbon fiber with a diameter of 7μm, tensile strength of 2.4GPa, and thermal conductivity of 800W / m·K as raw material to weave a high thermal conductivity fiber preform with a density of 0.8g / cm 3 A flat-plate-shaped high thermal conductivity fiber preform.
[0078] ② Preparation of porous carbon / carbon matrix: Chemical vapor deposition method was used to prepare pyrolytic carbon interface layer on the fiber surface of high thermal conductivity fiber preform, and the density of the prepared porous carbon / carbon matrix was 1.0 g / cm 3 porous carbon / carbon matrix.
[0079] ③ Preparation of a hafnium-zirconium composite ceramic precursor solution: The hafnium-zirconium composite ceramic precursor solution is prepared as follows: propyl hafnate and propyl zirconate (in an amount such that the molar ratio of hafnium in propyl hafnate to zirconium in propyl zirconate is 3:1) are uniformly mixed in xylene, followed by adding ninhydrin as a ligand (the molar ratio of propyl hafnate, propyl zirconate and ninhydrin is 3:1:3) and a phenolic epoxy vinyl ester resin (the molar ratio of propyl hafnate, propyl zirconate and phenolic epoxy vinyl ester resin is 3:1:10) and mixing them uniformly to obtain a mixed solution, and the mixed solution is reacted under an argon atmosphere at 5°C for 120 minutes to obtain the atomically uniformly mixed hafnium-zirconium composite ceramic precursor solution. The amount of xylene used is such that the solid content of the hafnium-zirconium composite ceramic precursor solution is 50% and the viscosity is 55 mPa·s.
[0080] ④ Preparation of ultra-high temperature ceramic-based composite materials: using hafnium-zirconium composite ceramic precursor solution as reactant, compounding porous carbon / carbon matrix, and preparing ultra-high temperature ceramic-based composite materials by precursor impregnation and cracking process, wherein the precursor impregnation and cracking process includes a specific impregnation-curing-cracking process as follows: placing porous carbon / carbon matrix in hafnium-zirconium composite ceramic precursor solution and sequentially performing vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes to obtain a material impregnated with hafnium-zirconium composite ceramic precursor solution, wherein the vacuum impregnation pressure is 200 Pa and the pressurized impregnation pressure is 1.5 MPa; then the obtained hafnium-zirconium composite ceramic precursor solution is solidified. The liquid-impregnated material was cured in a nitrogen atmosphere at a curing temperature of 260°C, a curing time of 120 minutes at 260°C, and a heating rate of 5°C / min to 260°C. The cured material was then placed in a reaction apparatus, sealed, evacuated, and introduced with nitrogen inert gas at a flow rate of 1000 sccm. The temperature was programmed to increase at a heating rate of 5°C / min, and the material was cracked at 1600°C for 240 minutes. After the cracking reaction was completed, the temperature was lowered at a rate of 5°C / min, cooled to room temperature, the nitrogen inert gas was turned off, and the material was returned to atmospheric pressure. The impregnation-curing-cracking process was repeated multiple times until a density of 3.9 g / cm was obtained. 3 Flat-plate ultra-high temperature ceramic matrix composite materials.
[0081] The fracture toughness of the ultra-high temperature ceramic matrix composite material prepared in this embodiment was measured to be 10.8 MPa·m at room temperature. 1 / 2 .
[0082] From the above examples 1 to 5, it can be seen that compared with example 1, the volume content of BN nanotubes used in example 2 is increased from 1% to 3%. Due to the increase in the volume content of BN nanotubes, the toughness of the ceramic matrix is significantly enhanced, so that the fracture toughness of the ceramic matrix composite material is increased from 27.3 MPa·m 1 / 2 Increased to 31.2MPa·m 1 / 2At the same time, the volume content of BN nanotubes increases, resulting in a decrease in the volume content of zirconium-hafnium-carbon solid solution, which reduces the ablation resistance of the composite material. The ablation rate of oxyacetylene wire increases from 1.0×10 -4 mm / s increased to 1.2×10 -4 mm / s; Compared with Example 1, the volume content of BN nanotubes used in Example 3 is reduced from 1% to 0.8%. Due to the decrease in the volume content of BN nanotubes, the toughness enhancement effect of the ceramic matrix is poor, resulting in the fracture toughness of the ceramic matrix composite material decreasing from 27.3 MPa·m 1 / 2 Reduced to 25.4 MPa·m 1 / 2 Compared with Example 1, Example 4 uses carbon nanotubes as the microscopic toughening phase. Since carbon nanotubes participate in the carbothermal reduction reaction to form a hafnium-zirconium-carbon solid solution, the carbon nanotube structure is damaged, and the toughness enhancement effect of the ceramic matrix is poor, resulting in the fracture toughness of the ceramic matrix composite material decreasing from 27.3 MPa·m 1 / 2 Reduced to 16.5 MPa·m 1 / 2 Compared with Example 1, Example 5 does not use BN nanotubes or carbon nanotubes as microscopic toughening phases, and the toughness of the ceramic matrix is poor, resulting in the fracture toughness of the prepared ceramic matrix composite material being reduced from 27.3 MPa·m 1 / 2 Reduced to 10.8 MPa·m 1 / 2 .
[0083] Examples 6 to 10
[0084] Examples 6 to 11 are basically the same as Example 1. The specific process parameters and the properties of the finally prepared ultra-high temperature ceramic-based composite materials are shown in Table 1 below. The other preparation processes are the same as those in Example 1.
[0085] Table 1
[0086]
[0087]
[0088] In Table 1, the symbol “ / ” indicates that the performance indicator was not tested.
[0089] As shown in Table 1, compared with Example 1, the aspect ratio of the BN nanotubes used in Example 6 is increased from 70 to 100. On the basis of keeping the length unchanged, the diameter is getting smaller, which makes the toughening effect of the ceramic matrix slightly worse, resulting in the fracture toughness of the ceramic matrix composite material from 27.3 MPa·m 1 / 2 Reduced to 26.8 MPa·m 1 / 2Compared with Example 1, the aspect ratio of the BN nanotubes used in Example 7 is reduced from 70 to 30. On the basis of keeping the length unchanged, the diameter is getting larger. It is no longer a one-dimensional tubular structure, which is not conducive to the toughness enhancement of the ceramic matrix, resulting in the fracture toughness of the ceramic matrix composite material decreasing from 27.3 MPa·m 1 / 2 Reduced to 20.7 MPa·m 1 / 2 Compared with Example 1, the length of the BN nanotubes used in Example 8 was reduced from 280 nm to 200 nm. On the basis of keeping the aspect ratio unchanged, the diameter was reduced, which slightly deteriorated the toughening effect of the ceramic matrix, resulting in the fracture toughness of the ceramic matrix composite material decreasing from 27.3 MPa·m 1 / 2 Reduced to 25.9 MPa·m 1 / 2 Compared with Example 1, the length of the BN nanotubes used in Example 9 is increased from 280 nm to 400 nm. On the basis of keeping the aspect ratio unchanged, the diameter is increased, which makes the toughening effect of the ceramic matrix slightly better. However, as the diameter of the BN nanotubes increases, the filling amount of the BN nanotubes is affected by the pore size in the porous carbon / carbon matrix, resulting in the fracture toughness of the ceramic matrix composite material decreasing from 27.3 MPa·m 1 / 2 Reduced to 21.6 MPa·m 1 / 2 Compared with Example 1, Example 10 only uses the sand milling process to disperse the BN nanotubes, which can only achieve coarse dispersion. The BN nanotubes still agglomerate, resulting in poor toughness enhancement of the ceramic matrix, resulting in the fracture toughness of the ceramic matrix composite material decreasing from 27.3 MPa·m 1 / 2 Reduced to 19.2 MPa·m 1 / 2 .
[0090] Example 11
[0091] ① Preparation of high thermal conductivity fiber preform: Using fine weaving puncture process, we use thin-diameter mesophase pitch-based carbon fiber with a diameter of 7μm, tensile strength of 2.4GPa, and thermal conductivity of 800W / m·K as raw material to weave a high thermal conductivity fiber preform with a density of 0.8g / cm 3 A flat-plate-shaped high thermal conductivity fiber preform.
[0092] ② Preparation of porous carbon / carbon matrix: Chemical vapor deposition method was used to prepare pyrolytic carbon interface layer on the fiber surface of high thermal conductivity fiber preform, and the density of the prepared porous carbon / carbon matrix was 1.0 g / cm 3 porous carbon / carbon matrix.
[0093] ③ Preparation of boron nitride nanotube-enhanced hafnium-zirconium composite ceramic precursor solution: The average length of the BN nanotubes (boron nitride nanotubes) used is 280 nm, and the average aspect ratio is 70; in the hafnium-zirconium composite ceramic precursor solution used, the atomic molar ratio of hafnium to zirconium is 3:1, the solid content of the hafnium-zirconium composite ceramic precursor solution is 50%, and the viscosity is 55 mPa·s. The hafnium-zirconium composite ceramic precursor solution used is prepared by: mixing propyl hafnate and propyl zirconate (in an amount such that the content of propyl hafnate is 100%) with propyl zirconate (in an amount such that the content of propyl hafnium ... zirconate is 100%) with propyl zirconate (in an amount The hafnium and zirconium propyl zirconate molar ratio is 3:1) are uniformly mixed in xylene, and then ninhydrin as a ligand (the molar ratio of hafnium propyl ester, zirconate propyl ester and ninhydrin is 3:1:3) and phenolic epoxy vinyl ester resin (the molar ratio of hafnium propyl ester, zirconate propyl ester and phenolic epoxy vinyl ester resin is 3:1:10) are added and mixed uniformly to obtain a mixed solution, and the mixed solution is reacted in an argon atmosphere at 5°C for 120 minutes to obtain the hafnium-zirconium composite ceramic precursor solution uniformly mixed at the atomic level. The hafnium zirconium composite ceramic precursor solution is prepared by uniformly dispersing BN nanotubes in the hafnium zirconium composite ceramic precursor solution by sand milling and high-pressure homogenization dispersion technology to obtain a hafnium zirconium composite ceramic precursor solution reinforced with boron nitride nanotubes. Specifically, the boron nitride nanotubes are added to the hafnium zirconium composite ceramic precursor solution and sand milled to obtain a coarse dispersion solution, and then the coarse dispersion solution is subjected to high-pressure homogenization dispersion to obtain the boron nitride nanotubes. Enhanced hafnium-zirconium composite ceramic precursor solution, the boron nitride nanotube-enhanced hafnium-zirconium composite ceramic precursor solution contains 1% by volume of boron nitride nanotubes; the sand milling time is 40 minutes, the sand milling speed is 2000 r / min, the particle size of the zirconium beads used in the sand milling is 1.8 mm, and the zirconium bead filling rate is 60%; the pressure (homogeneous pressure) of the high-pressure homogenization dispersion is 68 MPa, the high-pressure homogenization dispersion time is 30 minutes, and the temperature is 50°C.
[0094] ④ Preparation of high-toughness ultra-high-temperature ceramic matrix composite material: Boron nitride nanotube reinforced hafnium zirconium composite ceramic precursor solution is used as a reactant to composite a porous carbon / carbon matrix, and a precursor impregnation and pyrolysis process is used to prepare a flat plate-shaped high-toughness ultra-high-temperature ceramic matrix composite material containing a hafnium zirconium carbon solid solution ceramic matrix. The precursor impregnation and pyrolysis process includes a specific impregnation-curing-pyrolysis process: the porous carbon / carbon matrix is placed in the boron nitride nanotube reinforced hafnium zirconium composite ceramic precursor solution and vacuum impregnated for 60 minutes and pressurized for 60 minutes in sequence to obtain a material impregnated with the boron nitride nanotube reinforced hafnium zirconium composite ceramic precursor solution. The vacuum impregnation pressure is 200 Pa, and the pressurized impregnation pressure is 1. 5MPa; then the obtained boron nitride nanotube reinforced hafnium zirconium composite ceramic precursor solution impregnated material is cured in a nitrogen atmosphere, the curing temperature is 260 ° C, the curing time at 260 ° C is 120min, the heating rate to 260 ° C is 5 ° C / min, then the cured material is placed in a reaction device, sealed, evacuated, and nitrogen inert gas is introduced with a flow rate of 1000sccm. The program is set to control the temperature, the heating rate is 5 ° C / min, and the material is cracked at 1600 ° C for 240min. After the cracking reaction is completed, the temperature is lowered at a rate of 5 ° C / min, cooled to room temperature, the nitrogen inert gas is turned off, and the material is restored to atmospheric pressure; the impregnation-curing-cracking process is repeated many times until a density of 3.9g / cm is obtained. 3 The flat-shaped ultra-high temperature ceramic-based composite material is prepared. After the precursor impregnation and cracking process is completed, the flat-shaped ultra-high temperature ceramic-based composite material is further annealed three times using a Joule heat ultrafast synthesis process to finally obtain a flat-shaped high-toughness ultra-high temperature ceramic-based composite material; wherein, the Joule heat ultrafast synthesis process is carried out in a Joule ultra-fast heating device, the heating rate of each annealing treatment is 200°C / s, the annealing treatment is carried out in a nitrogen atmosphere, the annealing temperature is 1800°C, and the holding time for each annealing at 1800°C is 3 minutes. After the holding period is completed, it is naturally cooled to room temperature before the next annealing treatment is carried out.
[0095] The fracture toughness of the flat plate-shaped high-toughness ultra-high temperature ceramic matrix composite material finally obtained in this embodiment was measured to be 29.8 MPa·m at room temperature. 1 / 2 After the oxyacetylene ablation test at 2000℃ (ablation time is 500s), the linear ablation rate is 0.9×10 -4 mm / s.
[0096] Example 12
[0097] Example 12 is substantially the same as Example 11, except that:
[0098] ④ Preparation of ultra-high temperature ceramic-based composite materials: Boron nitride nanotube-reinforced hafnium-zirconium composite ceramic precursor solution is used as a reactant to compound the porous carbon / carbon matrix, and a flat-plate ultra-high temperature ceramic-based composite material containing a hafnium-zirconium-carbon solid solution ceramic matrix is prepared by a precursor impregnation and cracking process. The precursor impregnation and cracking process includes a specific impregnation-curing-cracking process as follows: placing the porous carbon / carbon matrix in a boron nitride nanotube-reinforced hafnium-zirconium composite ceramic precursor solution and sequentially performing vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes to obtain a material impregnated with a boron nitride nanotube-reinforced hafnium-zirconium composite ceramic precursor solution. The vacuum impregnation pressure is 200 Pa, and the pressurized impregnation pressure is 1.5 MPa. ; The obtained boron nitride nanotube reinforced hafnium zirconium composite ceramic precursor solution impregnated material is then cured in a nitrogen atmosphere at a curing temperature of 260°C, a curing time of 120 min at 260°C, and a heating rate of 5°C / min to 260°C. The cured material is then placed in a reaction device, sealed, evacuated, and introduced with nitrogen inert gas at a flow rate of 1000 sccm. The program is set to control the temperature at a heating rate of 5°C / min, and the material is cracked at 1600°C for 240 min. After the cracking reaction is completed, the temperature is lowered at a rate of 5°C / min, cooled to room temperature, the nitrogen inert gas is turned off, and the material is restored to atmospheric pressure. The impregnation-curing-cracking process is repeated multiple times until a density of 3.9 g / cm is obtained. 3 The flat-plate ultra-high temperature ceramic-based composite material is also subjected to annealing treatment after the precursor impregnation and cracking process is completed; wherein, the annealing treatment is carried out in a nitrogen atmosphere, the annealing temperature is 1800°C, the holding time at 1800°C is 9 minutes, and the heating rate to 1800°C is 10°C / min.
[0099] The fracture toughness of the ultra-high temperature ceramic matrix composite material finally obtained in this embodiment was measured to be 24.6 MPa·m at room temperature. 1 / 2 .
[0100] Example 13
[0101] ① Weaving fine-diameter mesophase pitch-based carbon fiber / carbon fiber bidirectional cloth: The fine-diameter mesophase pitch-based carbon fiber and PAN-based carbon fiber are mixed to obtain fine-diameter mesophase pitch-based carbon fiber / carbon fiber bidirectional cloth, so that the fine-diameter mesophase pitch-based carbon fiber and PAN-based carbon fiber are vertically distributed, and the surface density of the fine-diameter mesophase pitch-based carbon fiber / carbon fiber bidirectional cloth is 365g / m 2 The thin-diameter mesophase pitch-based carbon fiber used is a thin-diameter mesophase pitch-based carbon fiber with a diameter of 7 μm, a tensile strength of 2.4 GPa, and a thermal conductivity of 800 W / m·K.
[0102] ② Preparation of a pointed wedge-shaped high thermal conductivity fiber preform: A stacking and stitching process is adopted to obtain a pointed wedge-shaped high thermal conductivity fiber preform by weaving a thin-diameter mesophase pitch-based carbon fiber / carbon fiber bidirectional cloth. Specifically, the thin-diameter mesophase pitch-based carbon fiber / carbon fiber bidirectional cloth is first folded in half along a direction perpendicular to the thin-diameter mesophase pitch-based carbon fiber, and then multiple pieces of the folded thin-diameter mesophase pitch-based carbon fiber / carbon fiber bidirectional cloth are stacked and stitched to obtain a pointed wedge-shaped high thermal conductivity fiber preform; during the stacking, the tips of the folded thin-diameter mesophase pitch-based carbon fiber / carbon fiber bidirectional cloth correspond to the tips, and the thick ends correspond to the thick ends, and then PAN-based carbon fiber is used to stitch the stacked multiple pieces of the folded thin-diameter mesophase pitch-based carbon fiber / carbon fiber bidirectional cloth into one; the volume ratio of the thin-diameter mesophase pitch-based carbon fiber to the PAN-based carbon fiber in the obtained pointed wedge-shaped high thermal conductivity fiber preform is 2:1, and the density of the pointed wedge-shaped high thermal conductivity fiber preform is 0.75 g / cm 3 .
[0103] ③ Preparation of wedge-shaped porous carbon / carbon matrix: A pyrolytic carbon interface layer was prepared on the fiber surface of the wedge-shaped high thermal conductivity fiber preform by chemical vapor deposition method, and a density of 0.95g / cm 3 wedge-shaped porous carbon / carbon matrix.
[0104] ④ Preparation of boron nitride nanotube-enhanced hafnium-zirconium composite ceramic precursor solution: The average length of the BN nanotubes (boron nitride nanotubes) used is 280 nm, and the average aspect ratio is 70; in the hafnium-zirconium composite ceramic precursor solution used, the atomic molar ratio of hafnium to zirconium is 3:1, the solid content of the hafnium-zirconium composite ceramic precursor solution is 50%, and the viscosity is 55 mPa·s. The hafnium-zirconium composite ceramic precursor solution used is prepared by: mixing propyl hafnate and propyl zirconate (in an amount such that the content of propyl hafnate is 100%) with propyl zirconate (in an amount such that the content of propyl hafnium is 100%). The hafnium and zirconium propyl zirconate molar ratio is 3:1) are uniformly mixed in xylene, and then ninhydrin as a ligand (the molar ratio of hafnium propyl ester, zirconate propyl ester and ninhydrin is 3:1:3) and phenolic epoxy vinyl ester resin (the molar ratio of hafnium propyl ester, zirconate propyl ester and phenolic epoxy vinyl ester resin is 3:1:10) are added and mixed uniformly to obtain a mixed solution, and the mixed solution is reacted in an argon atmosphere at 5°C for 120 minutes to obtain the hafnium-zirconium composite ceramic precursor solution uniformly mixed at the atomic level. The hafnium zirconium composite ceramic precursor solution is prepared by uniformly dispersing BN nanotubes in the hafnium zirconium composite ceramic precursor solution by sand milling and high-pressure homogenization dispersion technology to obtain a hafnium zirconium composite ceramic precursor solution reinforced with boron nitride nanotubes. Specifically, the boron nitride nanotubes are added to the hafnium zirconium composite ceramic precursor solution and sand milled to obtain a coarse dispersion solution, and then the coarse dispersion solution is subjected to high-pressure homogenization dispersion to obtain the boron nitride nanotubes. Enhanced hafnium-zirconium composite ceramic precursor solution, the boron nitride nanotube-enhanced hafnium-zirconium composite ceramic precursor solution contains 1% by volume of boron nitride nanotubes; the sand milling time is 40 minutes, the sand milling speed is 2000 r / min, the particle size of the zirconium beads used in the sand milling is 1.8 mm, and the zirconium bead filling rate is 60%; the pressure (homogeneous pressure) of the high-pressure homogenization dispersion is 68 MPa, the high-pressure homogenization dispersion time is 30 minutes, and the temperature is 50°C.
[0105] ⑤ Preparation of pointed wedge-shaped high-toughness ultra-high temperature ceramic-based composite materials: Using boron nitride nanotube-reinforced hafnium zirconium composite ceramic precursor solution as a reactant, compounding the pointed wedge-shaped porous carbon / carbon matrix, and preparing a pointed wedge-shaped high-toughness ultra-high temperature ceramic-based composite material containing a hafnium zirconium carbon solid solution ceramic matrix through a precursor impregnation and cracking process. The precursor impregnation and cracking process includes a specific impregnation-curing-cracking process as follows: placing the pointed wedge-shaped porous carbon / carbon matrix in a boron nitride nanotube-reinforced hafnium zirconium composite ceramic precursor solution and sequentially performing vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes to obtain a material impregnated with a boron nitride nanotube-reinforced hafnium zirconium composite ceramic precursor solution, wherein the vacuum impregnation pressure is 200Pa and the pressurized impregnation pressure is 200Pa. The pressure is 1.5 MPa; the material impregnated with the obtained boron nitride nanotube-reinforced hafnium-zirconium composite ceramic precursor solution is then cured in a nitrogen atmosphere at a curing temperature of 260°C, a curing time of 120 minutes at 260°C, and a heating rate of 5°C / min to 260°C; the cured material is then placed in a reaction device, sealed, evacuated, and introduced with nitrogen inert gas at a flow rate of 1000 sccm; the temperature is set to be program-controlled at a heating rate of 5°C / min, and the material is cracked at 1600°C for 240 minutes. After the cracking reaction is completed, the temperature is lowered at a rate of 5°C / min, the material is cooled to room temperature, the nitrogen inert gas is turned off, and the material is restored to atmospheric pressure; the impregnation-curing-cracking process is repeated multiple times until a density of 3.9 g / cm is obtained. 3 A sharp wedge-shaped high-toughness ultra-high temperature ceramic matrix composite material.
[0106] The fracture toughness of the wedge-shaped ultra-high temperature ceramic matrix composite material obtained in this embodiment was measured to be 26.9 MPa·m at room temperature. 1 / 2 After the oxyacetylene ablation test at 2000℃ (ablation time is 500s), the linear ablation rate is 1.1×10 -4 mm / s.
[0107] Comparative Example 1
[0108] Comparative Example 1: A flat plate-shaped high-toughness ultrahigh temperature ceramic-based composite material was obtained by the same method as in Example 1, and then machined into a pointed wedge-shaped high-toughness ultrahigh temperature ceramic-based composite material.
[0109] The fracture toughness of the sharp wedge-shaped high-toughness ultra-high temperature ceramic matrix composite material obtained in this comparative example was measured to be 23.3 MPa·m at room temperature. 1 / 2 After the oxyacetylene ablation test at 2000℃ (ablation time is 500s), the linear ablation rate is 1.3×10 - 4 mm / s.
[0110] Comparative Example 2
[0111] ①Same as step ① of Example 13.
[0112] ② Preparation of a flat-plate high thermal conductivity fiber preform: A lamination and stitching process is adopted to weave a thin-diameter mesophase pitch-based carbon fiber / carbon fiber bidirectional cloth to obtain a flat-plate high thermal conductivity fiber preform. Specifically, multiple pieces of thin-diameter mesophase pitch-based carbon fiber / carbon fiber bidirectional cloth are stacked and stitched together to obtain a flat-plate high thermal conductivity fiber preform. The volume ratio of the thin-diameter mesophase pitch-based carbon fiber to the PAN-based carbon fiber in the obtained flat-plate high thermal conductivity fiber preform is 2:1, and the density of the flat-plate high thermal conductivity fiber preform is 0.75g / cm 3 ; The flat-plate-shaped high thermal conductivity fiber preform obtained in step ② is used to replace the wedge-shaped high thermal conductivity fiber preform in Example 13 to carry out the same subsequent steps ③, step ④ and step ⑤ as in Example 13.
[0113] The fracture toughness of the flat plate-shaped high-toughness ultra-high temperature ceramic matrix composite material obtained in this comparative example is measured to be 27.5 MPa·m at room temperature. 1 / 2 After the oxyacetylene ablation test at 2000℃ (ablation time is 500s), the linear ablation rate is 1.0×10 - 4 mm / s.
[0114] In this comparative example, the flat plate-shaped high-toughness ultrahigh temperature ceramic matrix composite material is machined into a pointed wedge-shaped high-toughness ultrahigh temperature ceramic matrix composite material, and the fracture toughness of the pointed wedge-shaped high-toughness ultrahigh temperature ceramic matrix composite material at room temperature is measured to be 22.9 MPa·m 1 / 2 After the oxyacetylene ablation test at 2000℃ (ablation time is 500s), the linear ablation rate is 1.4×10 -4 mm / s.
[0115] Although the performance of the flat-plate-shaped high-toughness ultra-high temperature ceramic-based composite material prepared in this comparative example is basically the same as that of the pointed wedge-shaped high-toughness ultra-high temperature ceramic-based composite material prepared in Example 13, when the flat-plate-shaped high-toughness ultra-high temperature ceramic-based composite material prepared in this comparative example is processed into a pointed wedge-shaped high-toughness ultra-high temperature ceramic-based composite material by traditional machining, this traditional method will cause the fibers in the tip area of the product to no longer be continuous, resulting in a significant decrease in the mechanical properties and ablation resistance of the pointed wedge-shaped high-toughness ultra-high temperature ceramic-based composite material.
[0116] Comparative Example 3
[0117] Comparative Example 3 is substantially the same as Example 1, except that:
[0118] ③ Preparation of boron nitride nanotube-enhanced hafnium-zirconium composite ceramic precursor solution: The average length of the BN nanotubes (boron nitride nanotubes) used is 280 nm, and the average aspect ratio is 70; the atomic molar ratio of hafnium to zirconium in the hafnium-zirconium composite ceramic precursor solution used is 3:1, the solid content of the hafnium-zirconium composite ceramic precursor solution is 50%, and the viscosity is 55 mPa·s. The preparation method is as follows: propyl hafnate and propyl zirconate (in an amount such that the molar ratio of hafnium in propyl hafnate to zirconium in propyl zirconate is 3:1) are uniformly mixed in xylene, and then ninhydrin as a ligand (the molar ratio of propyl hafnate, propyl zirconate and ninhydrin is 3:1:3) and phenolic epoxy vinyl ester resin (the molar ratio of propyl hafnate, propyl zirconate and phenolic epoxy vinyl ester resin is 3:1:10) are added and mixed uniformly to obtain a mixture. The invention relates to a method for preparing a hafnium-zirconium composite ceramic precursor solution comprising: adding the BN nanotubes to the hafnium-zirconium composite ceramic precursor solution, reacting the mixture under an argon atmosphere at 5° C. for 120 minutes, thereby obtaining an atomically uniformly mixed hafnium-zirconium composite ceramic precursor solution, wherein the amount of xylene used is such that the solid content of the hafnium-zirconium composite ceramic precursor solution is 50% and the viscosity is 55 mPa·s; and dispersing the BN nanotubes in the hafnium-zirconium composite ceramic precursor solution by stirring and ultrasonic treatment to obtain a boron nitride nanotube-reinforced hafnium-zirconium composite ceramic precursor solution. Specifically, the BN nanotubes are added to the hafnium-zirconium composite ceramic precursor solution, first stirred at a stirring speed of 400 rpm for 40 minutes, and then ultrasonically treated at a frequency of 20 kHz for 50 minutes to obtain a boron nitride nanotube-reinforced hafnium-zirconium composite ceramic precursor solution, wherein the boron nitride nanotube-reinforced hafnium-zirconium composite ceramic precursor solution contains 1% by volume of boron nitride nanotubes.
[0119] The fracture toughness of the ultra-high temperature ceramic matrix composite material finally obtained in this comparative example was measured to be 20.2 MPa·m at room temperature. 1 / 2 .
[0120] Comparative Example 4
[0121] ① is the same as step ① in Example 1.
[0122] ② is the same as step ② of Example 1.
[0123] ③ Preparation of boron nitride nanotube-enhanced hafnium-zirconium composite ceramic precursor solution: The average length of the BN nanotubes (boron nitride nanotubes) used is 280 nm, and the average aspect ratio is 70; the hafnium-zirconium composite ceramic precursor solution used has an atomic molar ratio of hafnium to zirconium of 3:1, and the solid content of the hafnium-zirconium composite ceramic precursor solution is 50%. The hafnium-zirconium composite ceramic precursor solution used is prepared by: mixing propyl hafnate and propyl zirconate (in an amount such that the hafnium in the hafnium ester and the zirconium in the zirconium ester are 1:1) with each other. The hafnium zirconium composite ceramic precursor solution was obtained by uniformly mixing the hafnium propyl ester, the zirconium propyl ester and the zirconium propyl ester in a molar ratio of 3:1) in xylene, and then adding acetylacetone as a ligand (the molar ratio of hafnium propyl ester, the zirconium propyl ester and the acetylacetone was 3:1:3) and allyl phenolic resin (the molar ratio of hafnium propyl ester, the zirconium propyl ester and the allyl phenolic resin was 3:1:10) and mixing them uniformly to obtain a mixed solution, and the mixed solution was reacted in an argon atmosphere at 15°C for 70 minutes to obtain a molecular-level mixed hafnium-zirconium composite ceramic precursor solution. The amount of the hafnium-zirconium composite ceramic precursor solution is such that the solid content of the hafnium-zirconium composite ceramic precursor solution is 50%; the BN nanotubes are uniformly dispersed in the hafnium-zirconium composite ceramic precursor solution by sand milling and high-pressure homogenization dispersion technology to obtain a boron nitride nanotube-reinforced hafnium-zirconium composite ceramic precursor solution, specifically, the boron nitride nanotubes are added to the hafnium-zirconium composite ceramic precursor solution and sand milled to obtain a coarse dispersion, and then the coarse dispersion is subjected to high-pressure homogenization dispersion to obtain the boron nitride nanotube-reinforced hafnium-zirconium composite ceramic precursor solution. The ceramic precursor solution comprises a boron nitride nanotube-enhanced hafnium-zirconium composite ceramic precursor solution, wherein the volume percentage of boron nitride nanotubes is 1%; the sand milling time is 40 minutes, the sand milling speed is 2000 r / min, the particle size of the zirconium beads used in the sand milling is 1.8 mm, and the zirconium bead filling rate is 60%; the pressure (homogeneous pressure) of the high-pressure homogenization dispersion is 68 MPa, the high-pressure homogenization dispersion time is 30 minutes, and the temperature is 50°C.
[0124] ④ Preparation of high-toughness ultra-high-temperature ceramic-based composite materials: Using the boron nitride nanotube-reinforced hafnium-zirconium composite ceramic precursor solution obtained in step ③ as a reactant, compounding the porous carbon / carbon matrix, and preparing a high-toughness ultra-high-temperature ceramic-based composite material by a precursor impregnation and pyrolysis process, the precursor impregnation and pyrolysis process includes a specific impregnation-curing-pyrolysis process: placing the porous carbon / carbon matrix in the boron nitride nanotube-reinforced hafnium-zirconium composite ceramic precursor solution and sequentially performing vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes to obtain a material impregnated with the boron nitride nanotube-reinforced hafnium-zirconium composite ceramic precursor solution, the vacuum impregnation pressure is 200 Pa, and the pressurized impregnation pressure is 1.5 MPa; The obtained boron nitride nanotube-reinforced hafnium-zirconium composite ceramic precursor solution was impregnated with the material and cured under a nitrogen atmosphere at a curing temperature of 260°C, a curing time of 120 minutes at 260°C, and a heating rate of 5°C / min to 260°C. The cured material was then placed in a reaction device, sealed, evacuated, and introduced with nitrogen inert gas at a flow rate of 1000 sccm. The temperature was controlled by a program at a heating rate of 5°C / min and cracked at 1600°C for 240 minutes. After the cracking reaction was completed, the temperature was lowered at a rate of 5°C / min, cooled to room temperature, the nitrogen inert gas was turned off, and the material was restored to atmospheric pressure. The impregnation-curing-cracking process was repeated multiple times until a density of 3.9 g / cm was obtained. 3 A flat plate-shaped high-toughness ultrahigh temperature ceramic matrix composite material comprising a hafnium carbide and zirconium carbide ceramic matrix.
[0125] The fracture toughness of the ultra-high temperature ceramic matrix composite material finally obtained in this comparative example was measured to be 26.4 MPa·m at room temperature. 1 / 2 After the oxyacetylene ablation test at 2000℃ (ablation time is 500s), the linear ablation rate is 1.6×10 -4 mm / s.
[0126] It can be seen from the comparison between Example 1 and Comparative Example 4 that by adopting the boron nitride-reinforced hafnium-zirconium composite ceramic precursor solution of the present invention as the impregnation liquid, a hafnium-zirconium-carbon solid solution ceramic matrix can be obtained in the ceramic-based composite material, which is beneficial to improving the ablation resistance and mechanical properties of the ceramic-based composite material.
[0127] Parts of the present invention that are not described in detail are well known to those skilled in the art.
[0128] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the various embodiments of the present invention.
Claims
1. A method for preparing a high-toughness ultra-high temperature ceramic-based composite material, characterized in that: The method comprises the following steps: (1) Preparation of high thermal conductivity fiber preform; (2) preparing an interface layer on the fiber surface of a high thermal conductivity fiber preform by chemical vapor deposition to obtain a porous carbon / carbon matrix; (3) Boron nitride nanotubes are uniformly dispersed in a hafnium zirconium composite ceramic precursor solution by sand milling and high-pressure homogenization dispersion technology to obtain a boron nitride nanotube-reinforced hafnium zirconium composite ceramic precursor solution; the hafnium zirconium composite ceramic precursor solution is prepared by: using xylene to uniformly mix hafnium propyl ester and zirconate propyl ester, then adding ninhydrin as a ligand and adding phenolic epoxy vinyl ester resin and mixing them uniformly to obtain a mixed solution, and reacting the mixed solution in an argon atmosphere at 5°C to 10°C for 100 to 150 minutes to obtain the hafnium zirconium composite ceramic precursor solution; (4) The boron nitride nanotube reinforced hafnium zirconium composite ceramic precursor solution was reacted with the porous carbon / carbon matrix through the precursor impregnation and cracking process to produce a high-toughness ultra-high temperature ceramic-based composite material.
2. The preparation method according to claim 1, characterized in that In step (1): The high thermal conductivity fiber preform is made of thin-diameter mesophase pitch-based carbon fibers, wherein the thin-diameter mesophase pitch-based carbon fibers have a diameter of 7-9 μm, a tensile strength of 2-3 GPa, and a thermal conductivity of 600-800 W / m·K; and / or The density of the high thermal conductivity fiber preform is 0.7-1.0 g / cm 3 .
3. The preparation method according to claim 1, characterized in that In step (2): The density of the porous carbon / carbon matrix is 0.9-1.2 g / cm 3 and / or The interface layer is one or more of a pyrolytic carbon interface layer, a boron nitride interface layer, and a silicon carbide interface layer.
4. The preparation method according to claim 1, characterized in that Step (3) is: adding boron nitride nanotubes to a hafnium-zirconium composite ceramic precursor solution and sand-milling the mixture to obtain a coarse dispersion, and then homogenizing the coarse dispersion under high pressure to obtain a fine dispersion, which is the boron nitride nanotube-reinforced hafnium-zirconium composite ceramic precursor solution; The sand milling time is 30-60 min, the sand milling speed is 1000-3000 r / min, the particle size of the zirconium beads used in the sand milling is 1-3 mm, and the zirconium bead filling rate is 50-70%; The pressure of the high-pressure homogenization dispersion is 35-100 MPa, the time of the high-pressure homogenization dispersion is 15-60 min, and the temperature is 25-60° C.
5. The preparation method according to claim 1, characterized in that In step (3): The length of the boron nitride nanotube is less than or equal to 300 nm, and the aspect ratio is greater than or equal to 60.
6. The preparation method according to claim 5, characterized in that In step (3): The hafnium-zirconium composite ceramic precursor solution has a solid content of 45-65% and a viscosity of 50-90 mPa·s; The boron nitride nanotube-enhanced hafnium-zirconium composite ceramic precursor solution contains 0.1-5% by volume of boron nitride nanotubes; The molar ratio of hafnium to zirconium in the hafnium-zirconium composite ceramic precursor solution is (0.1-99.9): (0.1-99.9); and / or The hafnium-zirconium composite ceramic precursor solution forms a hafnium-zirconium-carbon solid solution as a ceramic matrix during the precursor impregnation and cracking process.
7. The preparation method according to claim 1, characterized in that Step (4) includes the following sub-steps: (a) impregnating a porous carbon / carbon matrix in a boron nitride nanotube-reinforced hafnium-zirconium composite ceramic precursor solution for 10 to 360 minutes to obtain a material impregnated with the boron nitride nanotube-reinforced hafnium-zirconium composite ceramic precursor solution; (b) curing the material impregnated with the boron nitride nanotube-reinforced hafnium-zirconium composite ceramic precursor solution, and then placing it in a reaction device, sealing it, evacuating it, introducing an inert gas, and pyrolyzing it at 1500-1800° C. for 10-600 minutes; (c) After the cracking reaction in step (b) is completed, the temperature is lowered under program control, and after cooling to room temperature, the introduction of the inert gas is stopped, and the pressure is restored to atmospheric pressure; (d) Repeat steps (a) to (c) at least once.
8. The preparation method according to claim 7, characterized in that In step (a): The impregnation is vacuum impregnation and pressure impregnation.
9. The preparation method according to claim 7, characterized in that In step (b): The curing is performed at 150-350° C. for 10-360 minutes.
10. The preparation method according to claim 7, characterized in that In step (d): Repeat steps (a) to (c) 1 to 10 times.
11. The preparation method according to any one of claims 1 to 10, characterized in that In step (4), after the precursor impregnation and cracking process is performed, the method further includes the step of performing multiple annealing treatments using a Joule heat ultrafast synthesis process; The Joule heat ultrafast synthesis process is carried out in a Joule ultrafast heating device, with a heating rate of 180-260°C / s for each annealing treatment, an annealing temperature of 1600-2000°C, a holding time of 2-5 minutes for each annealing treatment, and natural cooling to room temperature after the holding period before the next annealing treatment; The annealing treatment is performed 3 to 5 times.
12. A high-toughness ultrahigh-temperature ceramic-based composite material prepared by the preparation method according to any one of claims 1 to 11.
13. The high-toughness ultrahigh-temperature ceramic-based composite material according to claim 12, characterized in that: The density of the high-toughness ultra-high temperature ceramic-based composite material is 3.0-5.0 g / cm 3 and / or The high-toughness ultra-high temperature ceramic-based composite material has a fracture toughness greater than or equal to 25 MPa·m at room temperature. 1 / 2 .
Citation Information
Patent Citations
High-toughness C / ultrahigh-temperature ceramic composite material and preparation method thereof
CN113582711A
Carbon-ceramic hybrid matrix gradient structure composite material and preparation method thereof
CN115611645A